The Effect of Using Two Styles of Individual Teaching in Acquiring & Retention the Technique of Performance some Basic skills in Volleyball - Hazim Ahmed Matrood (مجلة الرافدين للعلوم الرياضية, 2008)
The Study aimed to achieve the following : • Expounding the effect of using two styles of individual teaching (programmed teaching– personal teaching system) and traditional style in acquiring and retention the Technique of performance in some basic skills in volleyball. The following hypothesis in order to achieve the objectives of the study, the researchers set forth • No significant differences exist between using any of the two styles of individual teaching (programmed teaching – personal teaching system) and traditional style in aquriring and retention the art of performance in some basic skills in volleyball. The researchers adopted the experimental style that is appropriate for the study. The research sample consisted of (36) sophomore students in college of sport education at Mosul University for the term 2006-2007. The sample was randomly distributed into three groups of ( 12 students ) in each and each group received its special teaching style as following: a) The 1st experimental group : programmed teaching b) The 2nd experimental group : personal teaching system (Keller's Plan). c) The 3rd control group: traditional style of the teacher. The groups were homogenized according to the variables of (age, height, mass, and some physical and motion fitness elements) affected at learning some of the basic skills in volleyball. Two volleyball teaching programs were devised depending on references and specialists in teaching some basic skills in volleyball (setting the ball from above, passing from below, passing forward from the facing of head) according to the methods of (programmed instruction and personalized system of instruction) and the programs contain the curriculum of sophomore students. The time required to complete the education program lasted for (6) weeks starting at 9/11/2006 and ending on 28 / 12/ 2006 . using two teaching units per a week and the duration of each unit was (90) minutes . The data were collected and statistically analyzed using the statistical tools (arithmetic mean, standard deviation, multiple correlation coefficient, percentage , Anova one way and Duncan's test. The researchers concluded the following : 1. The two individual teaching system (programmed teaching – personal teaching system) in acquiring the Technique of performance of some basic skills of setting the ball from above , passing from below and passing forward from the head facing are more active than traditional style. 2. The tow individual teaching system (programmed teaching – personal teaching system) had a supremacy in the proportion of retention to the skills of (setting the ball from above , passing from below and passing forward from head facing to the applied traditional . The researchers recommended the following: 1- Applying the suggested teaching programs in teaching Volleyball skills in colleges and departments of sport education all over the universities in Iraq in accordance with the results research . 2 - When self teaching system is difficult to use in teaching some basic skills in volleyball, the programmed teaching style is preferred in order to achieve a level of performance better than when using the traditional styles.